CFD analysis of the thermal performance improvement in heat sinks with corrugated plate-fin. Issue 2 (November 2020) - Ghani, Ihsan Ali; Freegah, Basim; Hussain, Ammar A.
Abstract: A 3-dimensional numerical analysis is performed to study the thermal performance in three new designs of the corrugated plate-fin subjected to impinging airflow for Reynolds number range from 1600 to 7700. The three designs of pate-fin heat sink include a triangular (TRI-PFHS), a rectangular (REC-PFHS), and a semi-circular (SCR-PFHS). A comparative evaluation has been performed on the thermal performance of the suggested designs with the traditional type (T-PFHS). The results revealed that the thermal performance of new designs is higher than that of the traditional heat sink. The new designs of corrugated plate-fin heat sink have proved the ability to improve heat transfer due to the larger area offered by corrugation and high flow disruptions caused by the presence of a semi-confined channel. The performance of the new designs is assessed in terms of Nusselt number, pressure drop, and performance factor. The overall performance factor (Pf) for SCR-PFHS is predominant over all other designs which achieved a highest value of 1.76 at Re=7700.